2021
DOI: 10.1126/sciimmunol.abj1750
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 variants of concern partially escape humoral but not T cell responses in COVID-19 convalescent donors and vaccine recipients

Abstract: The emergence of SARS-CoV-2 variants harboring mutations in the spike (S) protein has raised concern about potential immune escape. Here, we studied humoral and cellular immune responses to wild type SARS-CoV-2 and the B.1.1.7 and B.1.351 variants of concern in a cohort of 121 BNT162b2 mRNA-vaccinated health care workers (HCW). Twenty-three HCW recovered from mild COVID-19 disease and exhibited a recall response with high levels of SARS-CoV-2-specific functional antibodies and virus-specific T cells after a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
412
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(471 citation statements)
references
References 93 publications
(120 reference statements)
28
412
0
3
Order By: Relevance
“…A recent study in Washington State indicated that VOC are overrepresented among post-vaccination breakthrough infections that do not require hospitalization [ 31 ]. As shown, mutations present in VOC, such as B.1.1.7 and B.1.351, do not escape the T-cell-mediated immunity that is elicited through vaccination [ 32 ]. Therefore, it is urgently needed to not rely solely on the antibody status level, but also to assess the cellular responses in vaccinated patients with severe breakthrough infections.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Washington State indicated that VOC are overrepresented among post-vaccination breakthrough infections that do not require hospitalization [ 31 ]. As shown, mutations present in VOC, such as B.1.1.7 and B.1.351, do not escape the T-cell-mediated immunity that is elicited through vaccination [ 32 ]. Therefore, it is urgently needed to not rely solely on the antibody status level, but also to assess the cellular responses in vaccinated patients with severe breakthrough infections.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study support previous findings indicating that protection against infection mediated by neutralizing antibodies may be impaired against the variants of concern, especially after a mild disease. While in the absence of neutralizing antibodies reinfection is possible, cellular immunity is not similarly affected by mutations in the RBD site (16) and is likely to provide long-term protection against severe disease.…”
Section: None Of These Individuals Had Documentation Of Pcr-confirmed Re-infection In the National Infectiousmentioning
confidence: 99%
“…The ongoing emergence of novel SARS‐CoV‐2 variants highlights the likely benefit of generating broad cellular and humoral immunity in response to vaccination. 1 , 2 , 3 Memory T cells play a critical role in protection against all viral pathogens. 4 They act directly by killing virally infected cells and also provide help for the maturation of B cells and their subsequent production of neutralising antibodies.…”
Section: Introductionmentioning
confidence: 99%